The Effect Of Performance Evaluation And Career Development On Employee Performance Mediated By Motivation To Work In The Office Sidikalang District Dairi Regency - Anny Fonisa Nasution; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2025)
Employee performance is influenced by various factors, including Performance Evaluation provided by the organization. Effective Performance Evaluation and proper Career Development can increase Motivation, which further contributes to improved performance. This study aims to identify the influence of Performance Evaluation and Career Development on Employee Performance by considering the role of Motivation as an intervening variable in the Sidikalang District Office, Dairi Regency. Data was obtained through a survey of employees with a quantitative approach and analyzed using the Partial Least Squares (PLS) method. The results of the analysis showed that Performance Evaluation had a positive and significant influence on work motivation, with a T-Statistic value of 1.227 and a P-Value of 0.000. Career Development also has a positive and significant influence on Work Motivation, with a T-Statistic value of 5.022 and a P-Value of 0.000. Work Motivation is proven to have a positive and significant influence on Employee Performance, with a T-Statistic value of 5.782 and a P-Value of 0.000, emphasizing the importance of Motivation as a performance driving factor. However, Performance Evaluation has a positive but not significant influence on Employee Performance, with a T-Statistic value of 0.957 and a P-Value of 0.000. Career Development also showed a positive but not significant influence on Employee Performance, with a T-Statistic value of 0.376 and a P-Value of 0.000. Indirect influence analysis showed that Work Motivation significantly mediated the relationship between Career Development and Employee Performance, with a T-Statistic value of 3.988 and an influence coefficient of 0.856. On the other hand, Work Motivation as a mediator in the relationship between Performance Evaluation and Employee Performance showed a not significant influence, with a T-Statistic value of 1.181 and an influence coefficient of 0.246. These findings indicate that improving Performance Evaluation and Career Development will be more effective in encouraging Employee Performance if facilitated by high work motivation.